Designing of a Micropump System for Circulatory Support - A. I. Khaustov; G. G. Boyarsky; K. V. Krotov (Известия высших учебных заведений России: Радиоэлектроника)
Introduction. Support systems currently used in modern cardiac surgery to provide partial or complete, permanent or temporary replacement of cardiac function are frequently characterized by large dimensions, thus requiring major surgical interventions. Low invasiveness can be ensured by reducing the size of the implanted part of such systems, allowing these devices to be inserted through the femoral artery.Aim. Development of a minimally invasive micropump system to support blood circulation.Materials and methods. Based on the analysis of implementation of micropump circulatory support systems (MCSS), the configuration, operational principles and main components of such a system were determined. When designing a micropump, as a unit defining the weight and size parameters of the entire system, numerical and experimental methods were used to optimize its flow path based on the condition of minimizing blood injury and thrombus formation. The lubrication and cooling system was developed by solving the thermodynamic problem of heat removal. The electronic control unit was developed on the basis of accumulated experience in the design and operation of control units for circulatory support systems.Results. A micropump with a diameter of 6.5 mm and a length of 43 mm with the required hydro- and hemodynamic parameters was designed. The device ensures minimal trauma and thrombus formation. The main MCSS parameters, as well as its main components (electric drives, lubrication and cooling systems), were defined. The configuration and operational principles of the electronic control unit (ECU), consisting in a microprocessor-based control system with feedback, were developed. The ECU built-in software manages the rotational speed of the electric drives of the micropump and coolant supply pump in the required range. In addition, the software is used to measure, display and register the MCSS operational parameters, as well as to monitor their operation in the required ranges and to exchange data between the ECU and the PC.Conclusion. All the necessary documentation for the MCSS nodes and components was prepared. These nodes and components ensure the hydro- and hemodynamic parameters required for the use of the developed minimally invasive micropump system. Future work will address the stages of MCSS assembly and debugging.